SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS PROBLEM-BASED LEARNING (PBL) BERBASIS SOCIO-SCIENTIFIC ISSUES (SSI) TERHADAP LITERASI SAINS DAN TREN PENELITIANNYA - Anisa Ramadhani; Assyifa’u Qolbiatu Atthoyibah; Hanifah Az-zahra; Mutia Haryani Siregar; Nadia Priska; Suci Ramadhani; Tariza Fairuz (STKIP Subang, 2026)
The low level of Indonesian students’ scientific literacy, which remains below the international benchmark, represents a critical challenge in contemporary science education. This study aims to systematically examine the trends and effectiveness of integrating Problem Based Learning (PBL) with Socio-Scientific Issues (SSI) in enhancing students’ scientific literacy. The study employs a Systematic Literature Review (SLR) approach guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Relevant articles were retrieved from the ScienceDirect and Google Scholar databases within the publication period of 2018–2026. The selection process, comprising identification, screening, and eligibility stages, resulted in a final corpus of 12 articles that met the predefined inclusion criteria.The findings indicate a substantial increase in scholarly publications during the 2024–2025 period, reflecting a growing academic interest in contextual and inquiry-based learning approaches. Furthermore, the analysis reveals strong conceptual linkages between scientific literacy, socio-scientific issues, and emerging educational trends such as Artificial Intelligence (AI). The synthesis of the selected studies demonstrates that the integration of PBL and SSI consistently contributes to moderate to high improvements in students’ scientific literacy. In addition, this instructional approach fosters higher-order thinking skills, particularly in argumentation and problem-solving, by engaging students with authentic, real-world issues.Overall, the integration of PBL and SSI provides a promising pedagogical framework for advancing scientific literacy and preparing students to address complex socio-scientific challenges in the modern era.